2013
DOI: 10.1209/0295-5075/104/17006
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear forward scattering by the 68.7 keV state of 73 Ge in CaGeO 3 and GeO 2

Abstract: We measured nuclear forward scattering of synchrotron radiation by the 68.7 keV nuclear resonance of 73Ge with a half-life . The Debye temperatures of CaGeO3 in the wollastonite, garnet and perovskite phases were determined to be 386(20) K, 437(20) K and 507(20) K, respectively, and 309(20) K and 459(11) K for GeO2 in the quartz and rutile phases, respectively. The isomer shift is clearly dependent on the Ge valence but not directly on the coordination geometry. The so far unknown magnetic moment μe of the 68.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…It must be noted that, in contrast to MS, NFS features no reference for the isomer shift and thus only differences in isomer shift between components Batteries & Supercaps can be measured, but not the isomer shift itself with reference to, e. g., the source or α-iron). [24] Analogous to Mössbauer spectroscopy results, a continuous increase in quadrupole splitting of both species upon desodiation reaction is observed. The reported absolute value of difference in isomer shift (Δ(δ)) of � 0.4 mms À 1 for component 2 and of 0.33 mm s À 1 for component 4 are in good agreement with the differences in isomer shift of the spectral contributions of Fe(III) and Fe(IV) observed in the conventional Mössbauer spectra for the intermediate and the EOC components, which confirms the formation of Fe(IV) upon desodiation.…”
Section: Simultaneous Nuclear Forward Scattering and X-ray Diffractionsupporting
confidence: 57%
“…It must be noted that, in contrast to MS, NFS features no reference for the isomer shift and thus only differences in isomer shift between components Batteries & Supercaps can be measured, but not the isomer shift itself with reference to, e. g., the source or α-iron). [24] Analogous to Mössbauer spectroscopy results, a continuous increase in quadrupole splitting of both species upon desodiation reaction is observed. The reported absolute value of difference in isomer shift (Δ(δ)) of � 0.4 mms À 1 for component 2 and of 0.33 mm s À 1 for component 4 are in good agreement with the differences in isomer shift of the spectral contributions of Fe(III) and Fe(IV) observed in the conventional Mössbauer spectra for the intermediate and the EOC components, which confirms the formation of Fe(IV) upon desodiation.…”
Section: Simultaneous Nuclear Forward Scattering and X-ray Diffractionsupporting
confidence: 57%
“…3b. The spectrum can be unambiguously explained by dynamical scattering that originates in the large nuclear effective thickness of the sample 32 . As in all other spectra we did not observe any quantum beats which could be attributed to magnetic ordering 31 .…”
Section: Nuclear Forward Scatteringmentioning
confidence: 92%
“…[8], thus seriously limiting the number of high energy Mössbauer transitions studied using synchrotron radiation. Other approaches were suggested to circumvent the pitfalls of silicon monochromators and thus the problem of non resonant detection overload, such as sapphire backscattering monochromatization [9][10][11][12], and nuclear lighthouse effect [13]. However, these approaches seriously limit the sample environment.…”
mentioning
confidence: 99%
“…It was previously shown that nuclear forward scattering around 70 keV can be carried out with medium resolution monochromatization of 30 [14] or even 100 meV [12]. The extension of this concept to higher energies in combination with an optimized detector system and the lower flux of synchrotron radiation above 80 keV highly reduces the need for sophisticated approaches to circumvent non resonant detection overload.…”
mentioning
confidence: 99%
See 1 more Smart Citation